Ecotheology and the Spirit of Ecology: A Comparative Study of World Religions and the Baduy Indigenous Tradition - Ruswanda, Asep Sandi (Prodi Studi Agama-Agama, 2026)
The contemporary global ecological crisis is driven by multiple factors, including a profound ethical crisis in the human-nature relationship. In this context, religious ethics assumes a significant normative responsibility. This study aims to analyze ecotheology as a form of religious ethics that embodies a spirit of ecology through a comparative approach encompassing both world religions and an indigenous religion. The research employs a qualitative method with a library research design and a conceptual-comparative analysis of theological sources within Islam, Protestantism, Catholicism, Hinduism, Buddhism, Confucianism, and the indigenous religion of the Baduy community, as well as academic scholarship addressing the relationship between religion and ecology. The findings indicate that each religious tradition possesses a robust ethical foundation for responding to the ecological crisis, albeit grounded in distinct theological and cosmological orientations. Islam, Protestantism, and Catholicism emphasize the theological mandate of humans as stewards of God’s creation through the concepts of khalifah, stewardship, and the notion of the common home as normative bases of ecotheology. Meanwhile, Hinduism, Buddhism, and Confucianism develop ecotheological perspectives rooted in relational cosmology, cosmic harmony, interdependence, and moral moderation. Beyond the world religions, the indigenous religion of Baduy demonstrates a lived and praxis-oriented form of ecotheology expressed through customary law, ecological taboos, and sustainability practices grounded in ancestral tradition. This article argues that ecotheology is not exclusive to a particular tradition but emerges across diverse religious communities, both world religions and indigenous faiths, as an inherent ethical framework aligned with the spirit of ecology